Production of defatted palm kernel cake protein hydrolysate as a valuable source of natural antioxidants - Zarei, Mohammad; Ebrahimpour, Afshin; Abdul Hamid, Azizah; Anwar, Farooq; Saari, Nazamid (MDPI, 2012)
The aim of this study was to produce a valuable protein hydrolysate from palm kernel cake (PKC) for the development of natural antioxidants. Extracted PKC protein was hydrolyzed using different proteases (alcalase, chymotrypsin, papain, pepsin, trypsin, flavourzyme, and bromelain). Subsequently, antioxidant activity and degree of hydrolysis (DH) of each hydrolysate were evaluated using DPPH• radical scavenging activity and O-phthaldialdehyde spectrophotometric assay, respectively. The results revealed a strong correlation between DH and radical scavenging activity of the hydrolysates, where among these, protein hydrolysates produced by papain after 38 h hydrolysis exhibited the highest DH (91 ± 0.1%) and DPPH• radical scavenging activity (73.5 ± 0.25%) compared to the other hydrolysates. In addition, fractionation of the most effective (potent) hydrolysate by reverse phase high performance liquid chromatography indicated a direct association between hydrophobicity and radical scavenging activity of the hydrolysates. Isoelectric focusing tests also revealed that protein hydrolysates with basic and neutral isoelectric point (pI) have the highest radical scavenging activity, although few fractions in the acidic range also exhibited good antioxidant potential.